2018
DOI: 10.1016/j.bbrep.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon resonance (SPR) based binding studies of refolded single chain antibody fragments

Abstract: Recent advances in Recombinant antibody technology / Antibody Engineering has given impetus to the genetic manipulation of antibody fragments that has paved the way for better understanding of the structure and functions of immunoglobulins and also has escalated their use in immunotherapy. Bacterial expression system such as Escherichia coli has complemented this technique through the expression of recombinant antibodies. Present communication has attempted to optimize the expression and refolding protocol of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…[36] . Singh [37] showed that Fab with lower K D value evinced better binding (1.5 fold higher) with the studied protein as compared to scFv. In addition, the results reported by Maruta et al [38] suggested that the binding activity of antibody fragments, especially scFv (higher K D ), might be slightly reduced in comparison to that of whole antibodies.…”
Section: Discussionmentioning
confidence: 97%
“…[36] . Singh [37] showed that Fab with lower K D value evinced better binding (1.5 fold higher) with the studied protein as compared to scFv. In addition, the results reported by Maruta et al [38] suggested that the binding activity of antibody fragments, especially scFv (higher K D ), might be slightly reduced in comparison to that of whole antibodies.…”
Section: Discussionmentioning
confidence: 97%
“…Compared to the Fab format, scFv with a smaller molecular size has proper folding and assembly in the periplasm of E. coli . The Fab format also tends to form homo-dimers, which leads to decreased solubility and reduced expression level of Fab in E. coli [ 32 , 33 ]. RBD as target molecules in the spike (S) protein are abundantly expressed on virus surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…SPR is a label-free biosensor technique for studying interactions between all classes of biomolecules and biochemical mechanisms in real time 29 . This is done in a label free environment, while the ligand of interest is immobilized on the surface of the sensor chip and solutions with different concentrations of the analyte can flow over it.…”
Section: Surface Plasmon Resonancementioning
confidence: 99%